Oxidative and nitrosative stress and apoptosis in oral mucosa cells after ex vivo exposure to lead and benzo[a]pyrene - Wannhoff, Andreas; Bölck, B.; Kübler, A. C.; Bloch, W.; Reuther, T. (Toxicology in vitro, 2013)
Exposure of human oral mucosa to lead (Pb) and benzo[a]pyrene (BaP) by inhalation and ingestion can lead to pathological conditions via apoptosis and oxidative and nitrosative stress. However, few studies have investigated the effects of Pb and BaP on oral mucosa cells. Furthermore, previous studies focused on chronic Pb and BaP exposure. Therefore, we evaluated important markers of apoptosis and oxidative and nitrosative stress in oral mucosa cells by incubating the cells with Pb and BaP for 5-360min. Ex vivo samples of human oral mucosa were exposed to Pb or BaP, and immunohistochemical staining was performed to evaluate active caspase-3, 8-epi-prostaglandin F2 alpha (8-epi-PGF2a), and 3-nitrotyrosine (3-NT). Pb and BaP treatments significantly increased active caspase-3 levels in a time-dependent manner. Furthermore, the treatments induced an early increase in 3-NT level, which ceased with longer incubation times. 8-Epi-PGF2a level increased only after prolonged incubation with Pb, and this elevation was irrespective of BaP incubation duration. Smokers’ samples had significantly lower levels of markers of oxidative and nitrosative stress than did nonsmokers’ samples. Thus, single, short-term exposure to Pb or BaP increases the levels of apoptosis markers and markers of oxidative and nitrosative stress.
Gesehen am 30.09.2021